Measuring Instrument for Self-Regulated Physics Learning at High School Level in Sungai Penuh - Netta, Nadia Alfia; Desnita, Desnita (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
Self-regulated learning in physics learning at school is very important. Which can influence self-regulated learning in following the learning process. To find out self-regulated learning, an instrument is needed. In fact, it is very difficult to find self-regulated learning assessment instruments in Physics subjects. Therefore, development research was carried out with the aim of developing a student self-regulated assessment instrument for Physics subjects. This type of research is research and development (R&D) developed by Sugiyono (2016). The sample for this research is students selected using the cluster random sampling method, namely samples from randomly selected classes, namely class XII MIPA for the 2023/2024 academic year at SMAN 2 Sungai Full. The analysis involved four expert lecturers who acted as validators. After it was valid, a trial of the instrument was carried out which was distributed to 114 students. Next, a trial test is carried out for the validity and reliability of a questionnaire. The results of the questionnaire trials that were distributed to students were analyzed using SPSS. Based on research and development from 30 statements, 28 valid questionnaire statements were obtained. Based on the analyzed questionnaire data, good validity was obtained for each question item. The reliability value obtained was (? = 0.9749).